Juridic Analysis of the Application of Legal Principles Contradictive Simple Proof in Two Identical Cases, hte Application for PKPU between Applicant PT Gugus Rimbarta and Requested PT Budikencana Megahjaya - Jahya Donny Adi Tampemawa; Moh Yuda Sudawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Whereas legal issues in the business/commerce world in Indonesia are increasingly complex the presence of the state is needed in facilitating the resolution of private conflicts in commerce. Whereas Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (UUK PKPU) is an effort by the State Administrators to prepare legal instruments in resolving debt and debt problems in the world of commerce. UUK PKPU Number 37 of 2004 is a special civil law instrument, where the lawsuit filed is a Petition/Volunteer and does not recognize the principle of Nebis In Idem (so that the same case can be applied repeatedly) and the formal process also does not recognize replicas, duplicates, compensation, exceptions (except regarding the authority to adjudicate) and intervention, and the application must be decided within 20 calendar days from the date the application is registered, whether the application for Whereas Case Number 51 and Case Number 211 are identical (same), because the Parties (the Petitioner and the Respondent) are the same, and the object of the debts and the arguments are the same, but in Case Number 51 the petition is rejected, while the petition for Case Number 211 is petition accepted, by implementing a simple contradictory principle of proof law, so that it has created legal uncertainty and undermined public confidence in the Commercial Court system at the Central Jakarta District Court. Whereas in December 2021, the Decision of the Constitutional Court Number 23/PPU-XIX/2021 essentially stated that the Debtor was allowed to file an appeal if the Creditor was a PKPU Petitioner, and the offer of reconciliation from the Debtor was rejected, so that the Respondent's Debtor had the opportunity to make efforts law at the Judex Juris level, so that it gets the opportunity to examine the legal considerations of judex fact.